(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2004)
A rapid and simple method for the simultaneous determination of nicotinamide, thiamine, pyridoxine, riboflavin and calcium pantothenate, associated with minerals was developed by high performance liquid chromatography. These vitamins were simultaneously assayed by reversed-phase ion-pair HPLC with C-8 column Perkin Elmer (150 x 4.6 mm, 5 mm, 80 Å) and UV detection (210 and 270 nm). A mobile phase of water-methanol (894:106), 10 mM hexanesulfonate, 0,5% acetic acid and 0,1% triethylamine at pH 3.5 allowed the most satisfactory separation of these vitamins. The method was successfully applied to the determination of vitamins in tablets and coated tablets. Linearity, precision, recovery and specificity were always satisfactory. The average recoveries were from 98% to 102% and the relative standard deviations were between 0.9 to 2.5%.